Severe asthma trajectories in adults: findings from the NORDSTAR cohort - von Bülow A; Hansen S; Sandin P; Ernstsson O; Janson C; Lehtimäki L; Kankaanranta H; Ulrik C; Aarli BB; Geale K; Tang ST; Wolf M; et al. (United Kingdom, 2025)
Background: There is limited evidence on the pathways leading to severe asthma and we are presently unable to effectively predict the progression of the disease. We aimed to describe the longitudinal trajectories leading to severe asthma and to describe clinical events preceding disease progression in a nationwide population of patients with severe asthma.
Methods: We conducted an observational study based on Swedish data from the NORdic Dataset for aSThmA Research (NORDSTAR) research collaboration platform. We identified adult patients with severe asthma in 2018 according to the European Respiratory Society/American Thoracic Society definition and used latent class analysis to identify trajectories of asthma severity over a 10-year retrospective period from 2018.
Results: Among 169 128 asthma patients, we identified 4543 severe asthma patients. We identified four trajectories of severe asthma that were labelled as: trajectory 1 "consistently severe asthma" (n=389 (8.6%)), trajectory 2 "gradual onset severe asthma" (n=942 (20.7%)), trajectory 3 "intermittent severe asthma" (n=1685 (37.1%)) and trajectory 4 "sudden onset severe asthma" (n=1527 (33.6%)). "Consistently severe asthma" had a higher daily inhaled corticosteroid dose and more prevalent osteoporosis compared with the other trajectories. Patients with "gradual onset severe asthma" and "sudden onset severe asthma" developed type 2-related comorbidities concomitantly with development of severe asthma. In the latter group, this primarily occurred within 1-3 years preceding onset of severe asthma.
Conclusions: Four distinct trajectories of severe asthma were identified illustrating different patterns of progression of asthma severity. This may eventually enable the development of better preventive management strategies in severe asthma.